Immediate Versus Standard Postpartum Screening for Diabetes [35B]. (May 2017) - Hsieh, Frances; Blitz, Matthew; Akerman, Meredith; Simmonds, Lisa; Rabin, Jill; Meirowitz, Natalie
Abstract : INTRODUCTION: Current guidelines recommend women with gestational diabetes undergo diabetes screening 6-12 weeks postpartum, however the compliance rate is only about 50%. Failure to return for care is a major barrier to postpartum screening. We sought to determine whether immediate postpartum screening is as reliable as standard postpartum screening at 6-12 weeks postpartum. METHODS: This was a prospective cohort study with women with singleton gestations and gestational diabetes (A1 or A2). Patients underwent a 2-hour 75-g oral glucose tolerance test (OGTT) on postpartum day 2, and were asked to repeat the OGTT at 6-12 weeks postpartum. The sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) of the immediate postpartum OGTT were calculated as compared to the gold standard, the OGTT at 6-12 weeks postpartum. Results were considered abnormal if either the fasting blood glucose (BG) value was greater than 100mg/dL or the 2-hour BG value was greater than 140mg/dL. RESULTS: 141 patients have been enrolled in the study. At this interim analysis, 70 completed the immediate postpartum screening for diabetes, and 53 returned for screening at the standard timeframe. Only the 53 patients with complete data were included in our analysis. The immediate OGTT had a sensitivity of 82.4%, specificity of 47.22%, NPV of 85.0% and PPV of 42.4%. CONCLUSION: Screening for diabetes immediately on postpartum day 2 is not a reliable substitute for screening at the current standard timeframe. Continued research with additional patients, and an analysis of clinical characteristics, may determine for which patients immediate screening is useful.